The Effect of Dexamethasone on Symptoms of Posttraumatic Stress Disorder and Depression After Cardiac Surgery and Intensive Care Admission: Longitudinal Follow-up of a Randomized Controlled Trial. Issue 6 (December 2016) - Kok, Lotte; Hillegers, Manon H.; Veldhuijzen, Dieuwke S.; Cornelisse, Sandra; Nierich, Arno P.; van der Maaten, Joost M.; Rosseel, Peter M.; Hofland, Jan; Sep, Milou S.; Dieleman, Jan M.; Vinkers, Christiaan H.; Peelen, Linda M.; et al.
Abstract : (Abstracted from Crit Care Med, 44:512–520, 2016) Cardiac patients admitted postoperatively to the intensive care unit may experience posttraumatic stress disorder and depression. Studies have shown an association between administering corticosteroids perioperatively and a reduction in the development of these conditions.